Theology of AIDS: a Lutheran / Moravian case study - Nurnberger, Klaus (Scriptura: Journal for Contextual Hermeneutics in Southern Africa, 2002)
This essay offers a critical introduction to the Lutheran / Moravian programme to combat the HIV / AIDS pandemic, drafted in March 2000, which has not been exposed to public debate as yet. It includes deep going theological reflection as well as a concrete plan of action : The law of God formulates the preconditions for a healthy human existence as revealed by observation and reason, rather than an authoritarian code of conduct. The gospel of Christ, understood as God's suffering, transforming acceptance of the unacceptable makes us ready to bear the cross with those who are infected and affected. The prophetic ministry has to focus on exposing and overcoming the hedonistic assumption of the modern commercial culture. The plan of action focuses on the establishment of AIDS Committees in each parish, which spread information, identify cases, and establish a local AIDS Support Group for each patient, based on the extended family and a caring community. Unwieldy and expensive bureaucracies are discouraged.
Free